Tingkat Adopsi Inovasi Teknologi Combine Harvester di Kelompok Tani Balong 01 Desa Tanjungbaru - Lulu Fazriah Intiaz; Agus Subhan Prasetyo; Kadhung Prayoga (Forum Agribisnis, 2022)
Rice is a staple food for Indonesian people, but the loss of crop yields is still relatively high. The loss of crop yields can be reduced by making improvements to the application of technology. Technological innovation in agriculture can increase agricultural productivity. The process of accepting technological innovation is defined as the adoption. Farmer’s adoption of agricultural technology is determined by the characteristic of the innovation, including relative advantage, compatibility, complexity, trialability, and observability. The study aims to analyze the rate of adoption of combine harvester innovation technology, analyze the characteristics of combine harvester innovation technology, and analyze the correlation between the adoption rate of combine harvester innovation technology with the characteristic of the innovation. This research was conducted in December 2021 until February 2022, located in Balong 01 Farmer Group, Tanjungbaru Village, East Cikarang District. The sampling method used was purposive sampling with the number of respondents as many as 29 members of the farmer group. Used data in the form of primary data and secondary data. Methods of data collection are done by interview, observation, and documentation. The data analysis method used was descriptive quantitative method in the form of Spearman-rank Correlation analysis. The result of the research showed that the level of farmer adoption in combine harvester innovation technology is in the high category. The level of characteristic of combine harvester innovation technology is in the high category. Between characteristics of innovation (relative advantage, compatibility, complexity, trialability and observability) and the level of farmer’s adoption showed a significant correlation. Suggestions for the future, for farmer group administrators and agricultural extension workers together carry out counseling or socialization related to comparing the actual results of using combine harvester with machines that were previously used in order to convince farmers of the advantages of combine harvester technology.